From Parents to Romantic Partners in a Globalized World: Coping with Relationship Stress in Adolescents from 20 Nations - Seiffge-Krenke, Inge (Adolescent Psychiatry, 2015)
Background: Both developmental and psychoanalytic theories stress the importance of romantic involvement for gaining autonomy from parents. It is, however, unclear whether the importance assigned to romantic affairs as well as the spill-over in parent-child relationships seen in Western countries can also be found in adolescents with other cultural backgrounds. In addition, the capacity to regulate distress in romantic encounters needs to be explored in adolescents from the majority world. Method: In a cross-cultural study on adolescents from 20 nations (N= 12.075), coping with stress in the family and romantic encounters was assessed in adolescents from seven regions of the world. The adolescents filled in instruments to asses stress in both domains as well as their coping behavior when stress in the family and the romantic domain emerged. Results: In general, levels of family-related stress as reported by adolescents were substantially higher than romantic stress in most regions. Particularly high were the family-related stress levels in adolescents from Southern Europe, Asia, the Middle East and South America. Adolescents from Central Europe and North America experienced lower stress with parents. As expected, adolescents were much more active in dealing with stress in the romantic domain than in the family domain, suggesting that differences in power balance did not allow for as much negotiating with parents as with the romantic partners. Conclusions: The results highlight that increasing autonomy is still a stressful task in most adolescents all over the world, leading to comparably high levels of parent-related stress. Coping with stress related to family relationships and romantic partnerships is a major focus; the amount of energy focused on each domain varies in accordance with cultural norms.
Keywords: coping